Applying invasion biology frameworks to predict the impacts of range‐expanding predators - Ryan A. Beshai; Paul E. Bourdeau; Lydia B. Ladah; Julio Lorda; Cascade J. B. Sorte (Ecology, 2026)
Global change is causing a widespread redistribution of species, and novel species are expected to impact populations in their recipient communities. Theory from invasion biology provides a framework to predict the impacts of range‐shifting species. Specifically, the impacts of invasive predators are expected to be nonlinear (greatest per capita effects at low densities) and to be greater in their invaded ranges when compared to their historical ranges. For range‐shifting species, we hypothesized that impacts would similarly be nonlinearly related to abundance and that impacts in the expanded range would be greater than those in the historical range (due to prey naivety and/or enemy release). Our alternative hypothesis was that impacts would be consistent between historical and expanded ranges (due to the potential for historical coevolutionary interactions with species in the expanded range). To test the applicability of this framework with range‐shifting species, we conducted observational surveys and manipulative experiments in the historical and expanded ranges of two predators undergoing poleward expansions, the whelks Acanthinucella spirata and Mexacanthina lugubris . We assessed impacts on prey (acorn barnacles and mussels) abundance and community diversity and compared per capita impacts between regions. As with non‐native invasive species, we found that both whelks reduced the abundance of prey species; however, our results supported a linear relationship and no decrease in per capita effect on prey with increasing density of the shifting predator, and we did not observe consistent impacts of range‐shifting whelks on community diversity. Finally, impacts in whelks' expanded ranges were generally consistent with those in historical ranges, with some potential for increased impact in the expanded range. By adapting invasion frameworks, our work revealed that abundance and impacts in the historical range are indicators of range‐shift impacts that could inform anticipatory management responses to range shifts.

Characteristics of positive parental effects under exposure to climate change in marine invertebrates - Heidi R. Waite; Cascade J. B. Sorte (Aquatic Ecology, 2025)

A Quantitative Classification of the Geography of Non‐Native Flora in the United States - Bethany A. Bradley; Annette E. Evans; Helen R. Sofaer; Montserrat Vilà; David T. Barnett; Evelyn M. Beaury; Dana M. Blumenthal; Jeffrey D. Corbin; Jeffrey S. Dukes; Regan Early; Inés Ibáñez; Ian S. Pearse; et al. (Global Ecology and Biogeography, 2025)
Aim Non‐native plants have the potential to harm ecosystems. Harm is classically related to their distribution and abundance, but this geographical information is often unknown. Here, we assess geographical commonness as a potential indicator of invasive status for non‐native flora in the United States. Geographical commonness could inform invasion risk assessments across species and ecoregions. Location Conterminous United States. Time Period Through 2022. Major Taxa Studied Plants. Methods We compiled and standardised occurrence and abundance data from 14 spatial datasets and used this information to categorise non‐native species as uncommon or common based on three dimensions of commonness: area of occupancy, habitat breadth and local abundance. To assess consistency in existing categorizations, we compared commonness to invasive status in the United States. We identified species with higher‐than‐expected abundance relative to their occupancy, habitat breadth or residence time. We calculated non‐native plant richness within United States ecoregions and estimated unreported species based on rarefaction/extrapolation curves. Results This comprehensive database identified 1874 non‐native plant species recorded in 4,844,963 locations. Of these, 1221 species were locally abundant (> 10% cover) in 797,759 unique locations. One thousand one hundred one non‐native species (59%) achieved at least one dimension of commonness, including 565 species that achieved all three. Species with longer residence times tended to meet more dimensions of commonness. We identified 132 species with higher‐than‐expected abundance. Ecoregions in the central United States have the largest estimated numbers of unreported, abundant non‐native plants. Main Conclusions A high proportion of non‐native species have become common in the United States. However, existing categorizations of invasive species are not always consistent with species' abundance and distribution, even after considering residence time. Considering geographical commonness and higher‐than‐expected abundance revealed in this new dataset could support more consistent and proactive identification of invasive plants and lead to more efficient management practices.

Using Plant Invasions to Compare Occurrence‐ and Abundance‐Based Calculations of Biotic Homogenisation: Are Results Complementary or Contradictory? - D. M. Buonaiuto; David Barnett; Dana M. Blumenthal; Andrea N. Nebhut; Ian S. Pearse; Helen R. Sofaer; Cascade J. B. Sorte; Jeffrey D. Corbin; Regan Early; Magda Garbowski; Ines Ibanez; Daniel C. Laughlin; et al. (Global Ecology and Biogeography, 2025)
Aim Beta diversity quantifies the similarity of ecological assemblages. Its increase, known as biotic homogenisation, can be a consequence of biological invasions. However, species occurrence (presence/absence) and abundance‐based analyses can produce contradictory assessments of the magnitude and direction of changes in beta diversity. Previous work indicates these contradictions should be less frequent in nature than in theory, but a growing number of empirical studies report discrepancies between occurrence‐ and abundance‐based approaches. Understanding if these discrepancies represent a few isolated cases or are systematic across a diversity of ecosystems would allow us to better understand the general patterns, mechanisms and impacts of biotic homogenisation. Location United States. Time Period 1963–2020. Major Taxa Studied Vascular plants. Methods We used a dataset of more than 70,000 vegetation survey plots to assess differences in biotic homogenisation with and without invasion using both occurrence‐ and abundance‐based metrics of beta diversity. We estimated taxonomic biotic homogenisation by comparing beta diversity of invaded and uninvaded plots with both classes of metrics and investigated the characteristics of the non‐native species pool that influenced the likelihood that these metrics disagree. Results In 78% of plot comparisons, occurrence‐ and abundance‐based calculations agreed in direction, and the two metrics were generally well correlated. Our empirical results are consistent with previous theory. Discrepancies between the metrics were more likely when the same non‐native species was at high cover at both plots compared for beta diversity, and when these plots were spatially distant. Main Conclusions In about 20% of cases, our calculations revealed differences in direction (homogenisation vs. differentiation) when comparing occurrence‐ and abundance‐based metrics, indicating that the metrics are not interchangeable, especially when distances between plots are high and invader diversity is low. When data permit, combining the two approaches can offer insights into the role of invasions and extirpations in driving biotic homogenisation/differentiation.

Biological modification of coastal pH depends on community composition and time - Cascade J. B. Sorte; Kristy J. Kroeker; Luke P. Miller; Matthew E. S. Bracken (Ecology, 2023)
Biological processes play important roles in determining how global changes manifest at local scales. Primary producers can absorb increased CO 2 via daytime photosynthesis, modifying pH in aquatic ecosystems. Yet producers and consumers also increase CO 2 via respiration. It is unclear whether biological modification of pH differs across the year, and, if so, what biotic and abiotic drivers underlie temporal differences. We addressed these questions using the intensive study of tide pool ecosystems in Alaska, USA, including quarterly surveys of 34 pools over 1 year and monthly surveys of five pools from spring to fall in a second year. We measured physical conditions, community composition, and changes in pH and dissolved oxygen during the day and night. We detected strong temporal patterns in pH dynamics. Our measurements indicate that pH modification varies spatially (between tide pools) and temporally (across months). This variation in pH dynamics mirrored changes in dissolved oxygen and was associated with community composition, including both relative abundance and diversity of benthic producers and consumers, whose role differed across the year, particularly at night. These results highlight the importance of the time of year when considering the ways that community composition influences pH conditions in aquatic ecosystems.

Biotic resistance or invasional meltdown? Diversity reduces invasibility but not exotic dominance in southern California epibenthic communities - Ryan A. Beshai; Danny A. Truong; Amy K. Henry; Cascade J. B. Sorte (Biological Invasions, 2023)
High community diversity may either prevent or promote the establishment of exotic species. The biotic resistance hypothesis holds that species-rich communities are more resistant to invasion than species-poor communities due to mechanisms including greater interspecific competition. Conversely, the invasional meltdown hypothesis proposes that greater exotic diversity increases invasibility via facilitative interactions between exotic species. To evaluate the degree to which biotic resistance or invasional meltdown influences marine community structure during the assembly period, we studied the development of marine epibenthic “fouling” communities at two southern California harbors. With a focus on sessile epibenthic species, we found that fewer exotic species established as total and exotic richness increased during community assembly and that this effect remained after accounting for space availability. We also found that changes in exotic abundance decreased over time. Throughout the assembly period, gains in exotic abundance were greatest when space was abundant and richness was low. Altogether, we found greater support for biotic resistance than invasional meltdown, suggesting that both native and exotic species contribute to biotic resistance during early development of these communities. However, our results indicate that biotic resistance may not always reduce the eventual dominance of exotic species.

Local-scale thermal history influences metabolic response of marine invertebrates to warming - Racine E. Rangel; Cascade J. B. Sorte (Marine Biology, 2022)

Dynamic species interactions associated with the range-shifting marine gastropod Mexacanthina lugubris - Piper D. Wallingford; Cascade J. B. Sorte (Oecologia, 2022)
Globally, species are undergoing range shifts in response to climate change. However, the potential impacts of climate-driven range shifts are not well understood. In southern California, the predatory whelk Mexacanthina lugubris has undergone a northward range shift of more than 100 km in the past four decades. We traced the history of the whelk’s range shift and assessed potential effects using an integrated approach, consisting of field surveys, as well as feeding and thermotolerance experiments. We found that at sites where Mexacanthina and native species co-occurred, native whelks distributions peaked lower in the intertidal. In laboratory experiments, we found that the presence of Mexacanthina led to reduced growth in native whelks ( Acanthinucella spirata ). Additionally, the range-shifting whelk was able to tolerate higher temperatures than common native species ( A. spirata and Nucella emarginata ), suggesting further impacts as a result of climate warming. Many species are likely to undergo range shifts as a coping mechanism for changing climatic conditions. However, communities are unlikely to shift as a whole due to species-specific responses. By studying the impacts of range-shifting species, like Mexacanthina , we can better understand how climate change will alter existing community structure and composition.

Negative carry‐over effects on larval thermal tolerances across a natural thermal gradient - Heidi R. Waite; Cascade J. B. Sorte (Ecology, 2022)
Under climate change, marine organisms will need to tolerate or adapt to increasing temperatures to persist. The ability of populations to cope with thermal stress may be influenced by conditions experienced by parents, by both genetic changes and transgenerational phenotypic plasticity through epigenetics or maternal provisioning. In organisms with complex life cycles, larval stages are particularly vulnerable to stress. Positive parental carry‐over effects occur if more stressful parental environments yield more tolerant offspring while the opposite pattern leads to negative carry‐over effects. This study evaluated the role of parental effects in determining larval thermal tolerances for the intertidal mussel, Mytilus californianus . We tested whether thermal environments across a natural gradient (shoreline elevation) impacted mussel temperature tolerances. Lethal thermal limits were compared for field‐collected adults and their larvae. We observed parental effects across one generation, in which adult mussels exposed to warmer habitats yielded less tolerant offspring. Interestingly, although parental environments influenced offspring tolerances, we found no clear effects of habitat conditions on adult phenotypes (tolerances). We found indicators of trade‐offs in energy investment, with higher reproductive condition and larger egg diameters in low stress environments. These results suggest that parental effects are negative, leading to possible adverse effects of thermal stress on the next generation.

Susan Lynn Williams: the Life of an Exceptional Scholar, Leader, and Friend (1951–2018) - William C. Dennison; Matthew E. S. Bracken; Maria Brown; John F. Bruno; James T. Carlton; Robert C. Carpenter; Tim J. B. Carruthers; Megan N. Dethier; Carlos M. Duarte; Thomas R. Fisher; James W. Fourqurean; Richard K. Grosberg; et al. (Estuaries and Coasts, 2021)
Susan Lynn Williams (1951–2018) was an exceptional marine ecologist whose research focused broadly on the ecology of benthic nearshore environments dominated by seagrasses, seaweeds, and coral reefs. She took an empirical approach founded in techniques of physiological ecology. Susan was committed to applying her research results to ocean management through outreach to decision-makers and resource managers. Susan’s career included research throughout the USA in tropical, temperate, and polar regions, but she specialized in tropical marine ecology. Susan’s scholarship, leadership, and friendship touched many people, leading to this multi-authored paper. Susan’s scholarship was multi-faceted, and she excelled in scientific discovery, integration of scientific results, application of science for conservation, and teaching, especially as a mentor to undergraduate and graduate students and postdoctoral scholars. Susan served in a variety of leadership positions throughout her career. She embodied all facets of leadership; leading by example, listening to others, committing to the “long haul,” maintaining trust, and creating a platform for all to shine. Susan was an important role model for women in science. Susan was also a loyal friend, maintaining friendships for many decades. Susan loved cooking and entertaining with friends. This paper provides an overview of the accomplishments of Susan in the broad categories of scholarship, leadership, and friendship.

Thermal tolerance limits as indicators of current and future intertidal zonation patterns in a diverse mussel guild - Cascade J. B. Sorte; Geneviève Bernatchez; K. A. S. Mislan; Lauren L. M. Pandori; Nyssa J. Silbiger; Piper D. Wallingford (Marine Biology, 2019)

Predicting persistence in benthic marine species with complex life cycles: linking dispersal dynamics to redistribution potential and thermal tolerance limits - Cascade J. B. Sorte; Lauren L. M. Pandori; Shukai Cai; Kristen A. Davis (Marine Biology, 2018)

Going with the flow: the role of ocean circulation in global marine ecosystems under a changing climate - Simon J. van Gennip; Ekaterina E. Popova; Andrew Yool; Gretta T. Pecl; Alistair J. Hobday; Cascade J. B. Sorte (Global Change Biology, 2017)
Ocean warming, acidification, deoxygenation and reduced productivity are widely considered to be the major stressors to ocean ecosystems induced by emissions of CO 2 . However, an overlooked stressor is the change in ocean circulation in response to climate change. Strong changes in the intensity and position of the western boundary currents have already been observed, and the consequences of such changes for ecosystems are beginning to emerge. In this study, we address climatically induced changes in ocean circulation on a global scale but relevant to propagule dispersal for species inhabiting global shelf ecosystems, using a high‐resolution global ocean model run under the IPCC RCP 8.5 scenario. The ¼ degree model resolution allows improved regional realism of the ocean circulation beyond that of available CMIP 5‐class models. We use a Lagrangian approach forced by modelled ocean circulation to simulate the circulation pathways that disperse planktonic life stages. Based on trajectory backtracking, we identify present‐day coastal retention, dominant flow and dispersal range for coastal regions at the global scale. Projecting into the future, we identify areas of the strongest projected circulation change and present regional examples with the most significant modifications in their dominant pathways. Climatically induced changes in ocean circulation should be considered as an additional stressor of marine ecosystems in a similar way to ocean warming or acidification.

Long‐term declines in an intertidal foundation species parallel shifts in community composition - Cascade J. B. Sorte; Victoria E. Davidson; Marcus C. Franklin; Kylla M. Benes; Meredith M. Doellman; Ron J. Etter; Robyn E. Hannigan; Jane Lubchenco; Bruce A. Menge (Global Change Biology, 2017)
The earth is in the midst of a biodiversity crisis, and projections indicate continuing and accelerating rates of global changes. Future alterations in communities and ecosystems may be precipitated by changes in the abundance of strongly interacting species, whose disappearance can lead to profound changes in abundance of other species, including an increase in extinction rate for some. Nearshore coastal communities are often dependent on the habitat and food resources provided by foundational plant (e.g., kelp) and animal (e.g., shellfish) species. We quantified changes in the abundance of the blue mussel ( M ytilus edulis ), a foundation species known to influence diversity and productivity of intertidal habitats, over the past 40 years in the Gulf of Maine, USA , one of the fastest warming regions in the global ocean. Using consistent survey methods, we compared contemporary population sizes to historical data from sites spanning >400 km. The results of these comparisons showed that blue mussels have declined in the Gulf of Maine by >60% (range: 29–100%) at the site level since the earliest benchmarks in the 1970s. At the same time as mussels declined, community composition shifted: at the four sites with historical community data, the sessile community became increasingly algal dominated. Contemporary (2013–2014) surveys across 20 sites showed that sessile species richness was positively correlated to mussel abundance in mid to high intertidal zones. These results suggest that declines in a critical foundation species may have already impacted the intertidal community. To inform future conservation efforts, we provide a database of historical and contemporary baselines of mussel population abundance and dynamics in the Gulf of Maine. Our results underscore the importance of anticipating not only changes in diversity but also changes in the abundance and identity of component species, as strong interactors like foundation species have the potential to drive cascading community shifts.

Space to invade? Comparative range infilling and potential range of invasive and native plants - Bethany A. Bradley; Regan Early; Cascade J. B. Sorte (Global Ecology and Biogeography, 2015)
Aim Our understanding of potential ranges for native and non‐native species is often based on their current geographic distributions. Non‐native species have had less time than co‐occurring native species to expand their ranges following introduction, so non‐native ranges may under‐represent suitable conditions. Therefore it is often assumed that species distribution models will predict disproportionately smaller potential ranges for non‐natives than natives. We compare the distributions of native, endemic, alien and invasive plants to determine how the different range attributes of these groups might influence ecological forecasting. Location Continental USA . Methods We compared the geographic ranges of 13,575 plant species (9402 native, 2397 endemic, 1201 alien and 755 invasive) using (1) US only and (2) global distribution data from herbarium records. We calculated US longitudinal and latitudinal range extents as potential indicators of range‐limiting factors, modelled potential range based on climate using principal components analysis, and calculated occupancy of potential ranges (range infilling). Results Contrary to expectations, modelled potential ranges were significantly larger for non‐natives than natives, even for species with few occurrences. Distributions of native species, not invasive species, appeared strongly limited longitudinally. However, invasive plants occupied substantially less area within their climatically suitable ranges than native plants (lower range infilling). Main conclusions Invasive plant distributions were consistently broader, both climatically and geographically, than comparable native species. This suggests that invasive plant distribution models at regional scales are not underpredicting potential ranges relative to models for native species. In contrast, the comparatively limited longitudinal ranges of native species suggest a high degree of non‐climatic limitation, which is likely to cause distribution models to underpredict the potential ranges of native species. Invasive plants have not achieved the degree of range infilling expected relative to natives. Thus, plants introduced to the US still have plenty of space to invade.

Poised to prosper? A cross‐system comparison of climate change effects on native and non‐native species performance - Cascade J. B. Sorte; Ines Ibáñez; Dana M. Blumenthal; Nicole A. Molinari; Luke P. Miller; Edwin D. Grosholz; Jeffrey M. Diez; Carla M. D'Antonio; Julian D. Olden; Sierra J. Jones; Jeffrey S. Dukes (Ecology Letters, 2013)
Climate change and biological invasions are primary threats to global biodiversity that may interact in the future. To date, the hypothesis that climate change will favour non‐native species has been examined exclusively through local comparisons of single or few species. Here, we take a meta‐analytical approach to broadly evaluate whether non‐native species are poised to respond more positively than native species to future climatic conditions. We compiled a database of studies in aquatic and terrestrial ecosystems that reported performance measures of non‐native (157 species) and co‐occurring native species (204 species) under different temperature, CO 2 and precipitation conditions. Our analyses revealed that in terrestrial (primarily plant) systems, native and non‐native species responded similarly to environmental changes. By contrast, in aquatic (primarily animal) systems, increases in temperature and CO 2 largely inhibited native species. There was a general trend towards stronger responses among non‐native species, including enhanced positive responses to more favourable conditions and stronger negative responses to less favourable conditions. As climate change proceeds, aquatic systems may be particularly vulnerable to invasion. Across systems, there could be a higher risk of invasion at sites becoming more climatically hospitable, whereas sites shifting towards harsher conditions may become more resistant to invasions.

Ocean warming increases threat of invasive species in a marine fouling community - Cascade J. B. Sorte; Susan L. Williams; Robyn A. Zerebecki (Ecology, 2010)
We addressed the potential for climate change to facilitate invasions and precipitate shifts in community composition by testing effects of ocean warming on species in a marine fouling community in Bodega Harbor, Bodega Bay, California, USA. First, we determined that introduced species tolerated significantly higher temperatures than natives, suggesting that climate change will have a disproportionately negative impact on native species. Second, we assessed the temperature dependence of survival and growth by exposing juveniles to an ambient control temperature and increased temperatures predicted by ocean warming scenarios (+3°C and +4.5°C) in laboratory mesocosms. We found that responses differed between species, species origins, and demographic processes. Based on the temperature tolerance, survival, and growth results, we predict that, as ocean temperatures increase, native species will decrease in abundance, whereas introduced species are likely to increase in this system. Facilitation of invasions by climate change may already be underway; locally, invasive dominance has increased concurrent with ocean warming over the past ∼40 years. We suggest that the effects of climate change on communities can occur via both direct impacts on the diversity and abundance of native species and indirect effects due to increased dominance of introduced species.

Marine range shifts and species introductions: comparative spread rates and community impacts - Cascade J. B. Sorte; Susan L. Williams; James T. Carlton (Global Ecology and Biogeography, 2010)
Aim Shifts in species ranges are a predicted and realized effect of global climate change; however, few studies have addressed the rates and consequence of such shifts, particularly in marine systems. Given ecological similarities between shifting and introduced species, we examined how our understanding of range shifts may be informed by the more established study of non‐native species introductions. Location Marine systems world‐wide. Methods Database and citation searches were used to identify 129 marine species experiencing range shifts and to determine spread rates and impacts on recipient communities. Analyses of spread rates were based on studies for which post‐establishment spread was reported in linear distance. The sizes of the effects of community impacts of shifting species were compared with those of functionally similar introduced species having ecologically similar impacts. Results Our review and meta‐analyses revealed that: (1) 75% of the range shifts found through the database search were in the poleward direction, consistent with climate change scenarios, (2) spread rates of range shifts were lower than those of introductions, (3) shifting species spread over an order of magnitude faster in marine than in terrestrial systems, and (4) directions of community effects were largely negative and magnitudes were often similar for shifters and introduced species; however, this comparison was limited by few data for range‐shifting species. Main conclusions Although marine range shifts are likely to proceed more slowly than marine introductions, the community‐level effects could be as great, and in the same direction, as those of introduced species. Because it is well‐established that introduced species are a primary threat to global biodiversity, it follows that, just like introductions, range shifts have the potential to seriously affect biological systems. In addition, given that ranges shift faster in marine than terrestrial environments, marine communities might be affected faster than terrestrial ones as species shift with climate change. Regardless of habitat, consideration of range shifts in the context of invasion biology can improve our understanding of what to expect from climate change‐driven shifts as well as provide tools for formal assessment of risks to community structure and function.

The impacts of climate change in coastal marine systems - Christopher D. G. Harley; A. Randall Hughes; Kristin M. Hultgren; Benjamin G. Miner; Cascade J. B. Sorte; Carol S. Thornber; Laura F. Rodriguez; Lars Tomanek; Susan L. Williams (Ecology Letters, 2006)
Anthropogenically induced global climate change has profound implications for marine ecosystems and the economic and social systems that depend upon them. The relationship between temperature and individual performance is reasonably well understood, and much climate‐related research has focused on potential shifts in distribution and abundance driven directly by temperature. However, recent work has revealed that both abiotic changes and biological responses in the ocean will be substantially more complex. For example, changes in ocean chemistry may be more important than changes in temperature for the performance and survival of many organisms. Ocean circulation, which drives larval transport, will also change, with important consequences for population dynamics. Furthermore, climatic impacts on one or a few ‘leverage species’ may result in sweeping community‐level changes. Finally, synergistic effects between climate and other anthropogenic variables, particularly fishing pressure, will likely exacerbate climate‐induced changes. Efforts to manage and conserve living marine systems in the face of climate change will require improvements to the existing predictive framework. Key directions for future research include identifying key demographic transitions that influence population dynamics, predicting changes in the community‐level impacts of ecologically dominant species, incorporating populations’ ability to evolve (adapt), and understanding the scales over which climate will change and living systems will respond.

Thermotolerance and heat-shock protein expression in Northeastern Pacific Nucella species with different biogeographical ranges - Cascade J. B. Sorte; Gretchen E. Hofmann (Marine Biology, 2005)